Axial fuel stratification of a homogeneous charge compression ignition (HCCI) engine - Aleiferis, Pavlos G.; Hardalupas, Yannis; Taylor, Alexander; Urata, Yasuhiro; Charalambides, Alexandros G. (My University, 2007)
Homogeneous charge compression ignition (HCCI) combustion is a method of internal engine combustion that incorporates principles from both spark ignition (SI) and compression ignition (CI) engines. The advantages of HCCI combustion are low NO x and soot emissions and high volumetric efficiency. Knocking at high loads is among the disadvantages of HCCI and fuel stratification can offer the possibility of reducing the knocking effect. In this study, infrared (IR) absorption was used to quantify the charge stratification in the engine, and pressure traces and fast camera images were acquired to investigate any variations between a strongly and a weakly stratified mixture.
Keywords: Imaging systems; Internal combustion engines; Fuel consumption